PKM GEMAR MAKAN IKAN UNTUK KECERDASAN ANAK SEKOLAH DI SDN 82/IV SEJINJANG KOTA JAMBI - Dini Junita; Dini Wulan Dari (Jurnal Abdimas Kesehatan (JAK), 2019)
Health efforts for children can be done through improving nutrition, especially in elementary school age. Good nutrition will produce quality human resources. One of the important nutrients for growth and development of school children is a protein derived from fish. This service activity applies leaflets and modules in conveying the message of the importance of fish consumption, involving the role of class teachers in transforming the benefits of fish consumption to students on an ongoing basis, exploring the factors that influence children in consuming fish. So that it is expected to increase the knowledge of the target and know the factors that influence the target in consuming fish. The results of this activity concluded that there was an increase in the knowledge of the target group about the importance of fish consumption, but it could not be ascertained the application in daily practice. So it needs to be monitored in its implementation. Knowledge and motivation are not the main factors children want to consume fish, the availability of food made from fish in the home and processing that can increase children's interest in fish consumption is the main factor that needs attention.